The oil and gas industry : exploration and production contracts - Omorogbe, Yinka (Lagos, Nigeria : Malthouse Press, 1997)
The book is about exploration, production and development of crude oil and the contract between the oil company and the host government.
Includes bibliographical references (p. [158]-161) and index.
rua 13/02/15
Loans
Keywords: Oil and gas leases; Petroleum law and legislation; Oil - production and exploration